53 BLUE TREATMENT FOR BLUE ANESTHESIA. (1st January 2006) - Mehr, A. J.; Askari, R.; Alsafwah, S.; Munir, A.
Abstract : Purpose: Methemoglobinemia is an uncommon but potentially fatal complication associated with topical anesthetics. We describe a case of methemoglobinemia-induced by topical benzocaine. Case: A 45-year-old male with transmetatarsal amputation due to diabetic neuropathy remained febrile despite appropriate antibiotics. On examination, a new 2/6 holosystolic apical murmur was heard at the apex in keeping with mitral valve incompetence. A transthoracic echocardiogram revealed anterior mitral leaflet thickening and a transesophageal echocardiogram was recommended for further diagnostic evaluation. Topical 20% benzocaine spray was administered to anesthetize the oropharynx. Before this procedure, oxygen saturation by pulse oximetry was 92% on room air, heart rate (HR) 105/min, and respiratory rate (RR) 18/min. Shortly thereafter, the patient became dyspneic and cyanotic while oxygen saturation fell to 84-86%; HR and RR increased to 120/min and 34/min, respectively; and he developed central cyanosis including mucous membranes. Oxygen did not relieve his breathlessness. Arterial blood gas (ABG) was obtained and blood was noted to be chocolate brown in color with oxygen saturation 97%. This "saturation gap, " which represents the difference between the high oxygen saturation from routine ABG analysis and the lower value measured by pulse oximetry, along with dark brown blood suggested methemoglobinemia. He was treated with intravenous 1 mg/kg of 1% methylene blue over 5 minutes with symptomatic relief within 30 minutes. Oxygen saturation on room air improved to 92% within 1 hour; he was observed overnight and remained stable and was discharged from the hospital several days later. There had been no personal or family history of cyanosis and the patient was not taking any medication (such as nitrates, sulfonamides, and phenytoin) known to cause methemoglobinemia. Conclusions: Benzocaine spray, widely used for topical anesthesia, may induce methemoglobinemia. This is due to its toxic metabolite, N-hydroxy derivative, whose aniline group can oxidize ferrous iron of heme to the ferric state, resulting in methemoglobin, which in high concentrations gives blood a chocolate-brown color. The diagnosis of methemoglobinemia is mainly clinical, with chocolate-colored blood being an important sign. Cooximetry is the diagnostic test of choice. Methylene blue acts as a reducing agent via the nicotinamide adenine dinucleotide phosphate (NADPH) methemoglobin reductase pathway. Hyperbaric oxygen and exchange transfusion are other alternate treatments. Removal of the inciting agent is most important.